Meeting Report: Key Outcomes from a Collaborative Summit on Agricultural Water Standards for Fresh Produce. Issue 3 (19th February 2019) - Wall, Gretchen L.; Clements, Donna P.; Fisk, Connie L.; Stoeckel, Donald M.; Woods, Kristin L.; Bihn, Elizabeth A.
Abstract: On February 27 to 28, 2018, the Produce Safety Alliance convened a national water summit in Covington, KY to discuss the requirements of the United States Food and Drug Administration's (FDA) Food Safety Modernization Act Standards for the Growing, Harvesting, Packing, and Holding of Produce for Human Consumption (Produce Safety Rule [PSR]). The goals of the meeting were to better understand the challenges growers face in implementing the requirements in Subpart E–Agricultural Water and work collaboratively to develop practical solutions to meet fruit and vegetable production needs while protecting public health. To meet these goals, the summit engaged a diverse group of stakeholders including growers, researchers, extension educators, produce industry members, and regulatory personnel. Key outcomes included defining implementation barriers due to diversity in water sources, distribution systems, commodity types, climates, farm size, and production activities. There was an articulated need for science‐based solutions, such as the use of agricultural water system assessments and sharing of federal, state, and regional water quality data, to ensure qualitative and quantitative standards reduce microbial risks. These identified challenges and needs resulted in significant debate about whether reopening the PSR–Subpart E for modification or attempting to address concerns through guidance would provide the best mechanism for alleviating concerns. In addition, training, outreach, and technical assistance were identified as vital priorities once the concerns are formally addressed by FDA. The water summit highlighted the critical need for transparency of FDA's progress on reevaluating the Subpart E requirements to help guide growers' decisions regarding the use of agricultural water.